Keeping an Open Mind About Evidence-Based Management: A Reply to Learmonth's Commentary - Rousseau, Denise M. (Academy of Management Review, 2006)
The article provides a response by D. M. Rousseau to Mark Learmonth's commentary on evidence-based management. Rousseau writes that evidence-based management should not be confused with “managerialism,” which she defines as the hierarchical system of management that exists in many corporations. Rousseau sees evidence-based management as a tool to help managers share power with workers, by avoiding arbitrary decision-making.